Parity equations for fault detection and isolation - Fagarasan, I.; St. Iliescu, S. (2008 IEEE International Conference on Automation, Quality and Testing, Robotics, 2008)
Sensors, actuators or physical components in engineering systems are often subjected to un-permitted or unexpected deviations from usual operating conditions. With a relatively small computing effort and with good results to unmeasured disturbances, the parity equations build for a specific process are proven to be very useful to provide fault detection residuals in order to identify the fault.